Gene flow, mating patterns and inbreeding depression in Roupala montana var. brasiliensis, a neotropical timber species - Pereira, Fernanda B. [UNESP]; Sebbenn, Alexandre M.; Boshier, David H.; Rossini, Bruno C. [UNESP]; Marino, Celso L. [UNESP]; Freitas, Miguel L. M.; Rosa, João R. B. F.; Vidal, Edson; Tambarussi, Evandro V. [UNESP] (Springer Nature, 2024)
Roupala montana var. brasiliensis is a timber tree species native to the Cerrado and Atlantic Forest areas of Brazil. The wood was exploited for international markets, but there is no information on the conservation status of its natural populations, nor on other key aspects, such as mating system, gene flow, and inbreeding depression, essential for the species’ sustainable management and conservation. We report the first study of any Roupala species to apply a validated set of species-specific microsatellite markers to genotype adults, juveniles, and seedlings, and analyse genetic diversity, inbreeding, effective population size, and mating system. We studied four populations of the species in areas of mixed Ombrophilous forest with different disturbance levels (undisturbed to strongly disturbed) in southern Brazil. The species occurs at low frequency in the study forests, but the populations are genetically diverse without significant differences in genetic diversity levels related to disturbance. The study also indicated resistance to the severe fragmentation associated with low density of individuals, with a stable mating system showing preferential outcrossing, with some inbreeding (tm ≈ 0.83, F > 0.165). Despite being spatially isolated from each other, the populations are not reproductively isolated, receiving immigrant pollen from long distances, although there was no evidence of gene flow into the populations via seeds. Seedlings from self-fertilization show low levels of inbreeding depression, which may reflect earlier pre-germination selection events. There was loss of allelic wealth in the younger cohorts, which may be a warning of the fragility of the genetic diversity detected in populations. We consider the implications of the results for the development of ex and in situ conservation and tree improvement programs.
Keywords: Atlantic forest; Brazilian lacewood; Conservation genetics; Genetic diversity; Mating system; Microsatellite markers; Spatial genetic structure